The Analysis of Ellipsis Found in Gary Dauberman’s Annabelle Comes Home - Asep Sugiarto; Andi Muhammad Irawan (English Language and Literature, 2022)
Communication is an activity that is always carried out by humans. In communicating, many people use ellipsis, where they omit part of the sentences they use. This research aims (1) to reveal the types of ellipsis found in Gary Dauberman's Annabelle Comes Home and (2) to reveal the classifications of sentences containing ellipsis in Gary Dauberman's Annabelle Comes Home. The research method used by researchers in this study was a qualitative method. The data source of this research is the Annabelle Comes Home movie. The research was conducted using the ellipsis theory proposed by Halliday and Hasan (1976) and the sentence classification theory by Frank (1972). The results showed that there were 81 uses of ellipsis, which included 7 nominal ellipsis, 12 verbal ellipsis and 62 clause ellipsis. The ellipsis were found in four sentence classifications. 56 uses of ellipsis were found in declarative sentences. In addition, in the interrogative sentence, 19 uses of ellipsis were found. Not only that, 5 uses of ellipsis were found in imperative sentences. Finally, in the exclamative sentence, only 1 use of ellipsis was found.